ANALISIS FENOMENOLOGI BANK MENDIRIKAN KOPERASI KREDIT - Dwiyoso, Hertoto; Susanto, M. Harri; Kaluge, David (Department of Economics, Faculty of Economics and Business, Universitas Brawijaya, 2008)
The approach used in this research is phenomenology as the object of the researchis a reality hidden in human awareness. The analysis process of findings in thisresearch is based on interactive model of analysis by Miles and Huberman, andsome idea from Husserl, Weber, Schutz and Berger. Moreover, it is necessary toappreciating this reality with a fully comprehension (verstehen) because thetrue reality hidden in human awareness. Some significant findings are found inthis research. First, the reality that the bank establishing credit cooperationappears in phases of interaction and deeply thought, and also as reflection ofother interconnected realities. Second, the goal in establishing credit cooperationis for the sake of satisfying the desire for getting profit as many as possible. Thecooperation is used as a mask covering the real fact that it is only a mean foravoiding the regulation. Third, the act of establishing credit cooperation isactually an effort to legalize the practice of bank inside bank as the practiceinvolved is the same, but now it has legally cooperation practice.Keywords: agency problem, the practice of bank inside bank, credit cooperation.